Kadirun Yahya: A Perspective from Quranic Studies - Herianto; Zulfi Imran (Cattleya Darmaya Fortuna, 2026)
Advancements in science and technology have spurred the emergence of various paradigms seeking to integrate science with spiritual values. One such concept developed in Indonesia is the